Biological Uptake of Phosphorus by Activated Sludge - Yall, Irving (1970)
The ability of activated sludge to remove phosphates was studied by adding carrier-free (32)P to raw sewage and measuring incorporation of the radioactivity into the cells over a period of time. Radioisotope determinations indicated that 48% of the (32)P radioactivity was removed by 12 hr. However, chemical methods indicated that only 30% of the orthophosphate apparently disappeared from the sewage during this period. Experiments with sludge prelabeled with (32)P indicated that considerable phosphate turnover occurred. The cells released large amounts of radioactivity as they were incorporating fresh phosphates. Starvation in isotonic saline for 18 hr caused the sludge to dump phosphate. When introduced into fresh sewage containing (32)P, the starved sludge removed about 60% of the radioactivity in 6 hr with little phosphate turnover. The ability of sludge to remove (32)P was inhibited approximately 83% by 10(−3)m 2,4-dinitrophenol. This inhibition was at the expense of the cell fraction that contained ribonucleic acid and deoxyribonucleic acid. The sludge cells released orthophosphate when exposed to the chemical agent. Experiments using (45)Ca indicated that calcium phosphate precipitation plays a minor role in phosphate removal under our experimental conditions.